The Correlation of Age and Knowledge on Behavior to Take the Supplement during The COVID 19 Pandemic (Study Case: in Kecamatan Selat, Kabupaten Kapuas) - Hawini, Laudia; Yuwindry, Iwan; Riduansyah, Muhammad (Faculty of Pharmacy, Widya Mandala Surabaya Catholic University, Indonesia, 2023)
Changes in people's lifestyles and consumption patterns during the COVID-19 pandemic led to an increase in the use of supplements. Supplements are basically taken to supplement nutrition, not to replace it. Age is known to have an effect on knowledge and behavior of supplement consumption. Researchers want to know the relationship between age and level of knowledge and behavior of using supplements during the Covid 19 pandemic. The research design used was cross sectional with analytical observational research. The population and sample are people who use supplements in the Selat District of Kapuas Regency in November 2020-July 2021, totaling 44 people. This study aims to determine the relationship between age and knowledge and behavior of using supplements during the Covid 19 pandemic in the Selat District, Kapuas Regency. Based on data analysis, it was found that there was no relationship between age and knowledge (p=0.264 > 0.05) and there was no relationship between age and behavior (p=0.538 > 0.05). So it can be concluded that age has no effect on knowledge and behavior of using supplements during the Covid 19 pandemic in the Straits District of Kapuas Regency.